2014
DOI: 10.1021/la500805d
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Suppression of the “Coffee Stain Effect”

Abstract: The dynamics of a slender, evaporating, particle-laden droplet under the effect of electric fields are examined. Lubrication theory is used to reduce the governing equations to a coupled system of evolution equations for the interfacial position and the local, depth-averaged particle concentration. The model incorporates the effects of capillarity, viscous stress, Marangoni stress, elecrostatically induced Maxwell stress, van der Waals forces, concentration-dependent rheology, and evaporation. Via a parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…We note that, as viewed from the ‘outer' region, the interface is located at z =0+ O (). Dropping the tilde decoration, this ultimately leads to the governing equations26,…”
Section: Methodsmentioning
confidence: 99%
“…We note that, as viewed from the ‘outer' region, the interface is located at z =0+ O (). Dropping the tilde decoration, this ultimately leads to the governing equations26,…”
Section: Methodsmentioning
confidence: 99%
“…the use of electric fields. [16][17][18][19] Nevertheless, the mechanisms through which surfactants affect the evaporation process are not well understood and have been a topic of debate. It has been suggested that surfactants can be responsible for suppressing the effect of thermal Marangoni flow by generating a counter gradient of surface tension driving liquid outwards.…”
mentioning
confidence: 99%
“…After balancing the conductive heat within the film with the heat dissipated through evaporation, we arrive at a scaling factor for j, j=kΔT/h0La, where k is the thermal conductivity of the film and La is the latent heat of vaporization for the solvent. As have previous works, we assume that the film's thermal conductivity is independent of film composition . The dimensionless temperature boundary conditions for the film are: T=1 at z=hb, Tz=j=T/K at z=h, where K is the rescaled constant for the one‐sided evaporation model in eq , K=K/(h0La/k).…”
Section: Mathematical Modelmentioning
confidence: 99%